Effect of plastic composition in the combustion material on the Persistent Organic Pollutant content in smoked chicken meat - Giang Do Hoang; Uyen Nguyen Thu; Luyen Nguyen Thi; Duong Hoang Thuy; Le Bui Thi Nhat; Nam Vu Duc; Xuyen Nguyen Thi; Thuy Le Minh; Tuan Anh Hoang Le; Tung Nguyen Ngoc; Dat Nguyen Tien (PLoS ONE, 2026)
Traditional food smoking in Vietnam often uses biomass fuels, but the incidental inclusion of plastics can generate toxic pollutants. This study evaluated the effects of polyethylene (PE), polystyrene (PS), and polyvinyl chloride (PVC) compared with clean wood on persistent organic pollutants (POPs) in smoked chicken, including PCBs, PCDD/Fs, and PAHs. Samples were smoked under controlled conditions, analyzed by GC–MS/MS, and assessed with univariate and multivariate statistics. Clean wood yielded low contamination, while PE introduced lighter PAHs and dioxins, PS was associated with mid-weight PAHs and specific PCBs (66, 195), and PVC caused the most severe contamination with 12 PCDD/Fs, 21 PCBs (e.g., 189, 101, 180, 153), and multiple carcinogenic PAHs (e.g., benzo[a]pyrene). Statistical tests confirmed significant differences among fuel groups (p < 0.01). The contamination gradient (W < PE < PS < PVC) highlights the urgent need to prohibit plastic-contaminated fuels in traditional smoking to safeguard food safety and public health.